Predisposing factors towards risk-taking behaviours among in-school adolescents in Ibadan metropolis, Oyo State, Nigeria (2016)
The percentage rate of violence and societal menace rampant in the society today has been recorded to be a by-product of adolescent risk related behaviours. This created an interest in the investigation of predisposing factors towards risk-taking behaviours among in-school adolescents in Ibadan metropolis. The study adopted a correlational research design with a randomly sampled 300 male and female in-school adolescents. Data were collected, using questionnaire measuring family dynamics (Inventory of parent and peer attachment (α=0.78), self-esteem (Rosenburg self-esteem scale (a=0.76), school connectedness (Youth transition survey (α=0.77) and risk-taking behaviour (Youth at-risk and general stability survey (α=0.82). Three research questions were raised and answered. The data were analysed using Pearson's Product Moment Correlation and Multiple Linear Regression at 0.05 level of significance. Result revealed a positive correlation between risk-taking behaviour and self-esteem and negative correlation with family dynamics and school connectedness. High family dynamics and school connectedness will reduce the likelihood of students engaging in risk-taking behaviours. The result also showed that three predictor variables (family dynamics, self-esteem and school connectedness) are potent predictors of risk-taking behaviour F (3,396) = 6.875, R' 85, =P<0.001). The most potent factor was family dynamics, followed by school connectedness and self-esteem. Counseling intervention, such as self-monitoring, peer pressure management, self-regulation, values clarification, and thought-stopping, could help adolescents to withstand the likely effects of low family dynamics, school connectedness and high self-esteem all of which are implicated in this study. Finally, in-school adolescents from a positive family background and a high connection to school may not likely engage in risk-taking behaviours as a result of positive attitude they imbibe both from home and school. School programmes and counselling activities should be channeled towards building students' interest in schooling. Parents are also enjoined to provide social support to the adolescents by showing love, warmth, care and affection.